"Navigating the Indo-Pacific Chessboard: Understanding the USA's Indo-Pacific Strategy and Its Implications on India" - Dr. Vimal Nayan Pandey and Ashutosh Kumar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The Indo-Pacific region contains the world's most demographic and economically dynamic countries, which have a captivating history, abundant intrinsic beauty, significant human capital, and extensive resources. Shinzo Abe, who was the prime minister of Japan, delivered a speech in 2007 to the Indian Parliament in which he originally coined the term "Indo-Pacific''. Barack Obama adopted this term in his final month of administration as the president of the United States of America and incorporated it into their strategic vision. Gradually, the region has become a very important component of U.S. strategic policy. For dominance, the US administration has increasingly focused on the Indo-Pacific region. This process is aligned with the global security that the U.S. is committed to encouraging the country to form alliances with both regional and international partners. In this regard, this paper aims to present a theoretical framework of US strategy in the region and its implication on India and analyse the trends of the US-India relationship. This article tries to examine the security dilemmas, economic interests, and soft power dynamics in the region in the context of US strategy and its impact on India. This article sheds light on India's foreign policy, regional leadership, and multifaceted partnership providing a complete understanding of the Indo-Pacific strategy of the USA. This article provides a comprehensive lens for analysing US Indo-Pacific strategy and it also provides valuable insights into economic dynamics and their implications for India.